Nasalidade na comunidade de fala de Fortaleza dos Nogueiras-MA - SANTOS, Gisélia Brito dos (2009)
This paper presents an analysis of the nasality in the speech community of Fortaleza Nogueiras-MA, is which the postulates of the structuralism and generative theory are used to present nasal phonemes in the Portuguese language in Brazil and particulary in the analyzed corpus. The informants of this research are people with low formal education, who have always lived in rural areas, and they are over 60 years old. The Field Research was used in the data collection, phonographic transcription in the record, and the analytical descriptive method to analyze them. The theoretical framework presents issues related to Phonetics, mainly the Articulatory Phonetics; the Phonology, especially the Linear Phonology; and Morphology, with issues related to the definition and formation of words, particularly in diminutive and augmentative degree. We present a historical overview of consonants and vowel phonemes, in which we have focused the nasal phonemes, and their transformations, from Latin to Portuguese. With respect to Brazilian Portuguese, we describe the nasality from the conception of nasal phonemes of Camara Jr. (1970), also the progressive and regressive spreading concepts and the nasality treatment within the syllable. The main focus for this analysis is the progressive and regressive spreading of nasal resonance, from the three nasal consonant phonemes, that belongs to the Portuguese language / m /, / n / e // in grammatical and phonological words. For this analysis, it was considered the intralingual aspects as phonetic-phonological environmental, stress, syllable structure, words boundaries, grammatical and phonological words. We have discussed the nasality in the formation of diminutives and augmentative degrees and, lastly, we have presented some progressive and regressive nasalization rules, based on the features model proposed by Chomsky and Halle (1968 apud MATZENAUER)